Electro-optical display and composite material with low thermal sensitivity used therein

By using composite materials of polymer phase and filler phase in the adhesive material of electro-optic display, the problem of image quality degradation caused by particle settlement in the electrophoretic display is solved, and the effect of maintaining good performance over a wider temperature range is achieved.

CN116420116BActive Publication Date: 2025-03-25E INK CORP
View PDF 200 Cites 0 Cited by

Patent Information

Application Number
CN202080105468.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-29
Publication Date
2025-03-25
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

The image quality of existing electro-optical displays has decreased in long-term use, especially the service life of electrophoretic displays based on particles is insufficient due to particle settlement.

Method used

A composite material containing a polymer phase and a filler phase is used as the binder material for the electro-optical display. The volume fraction of the filler phase is about a percolation threshold, and the ratio of the thermal expansion coefficient of the filler to the polymer is less than or equal to 0.5 to limit the temperature dependence of the conductivity.

Benefits of technology

Improves the performance of electro-optical displays over a wider ambient temperature range, reduces the instability of conductivity with temperature variation, and thus extends the life of the display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116420116B_ABST
    Figure CN116420116B_ABST
Patent Text Reader

Abstract

An electro-optical display comprises an electro-optical material layer, at least one conductor, and an adhesive material between the electro-optical material layer and the at least one conductor. At least one of the electro-optical material and the adhesive material comprises a composite material, the composite material comprising a polymer phase and a filler phase, the filler phase having a molecular weight greater than or equal to 0.5×10 3 The electrical conductivity of the composite material is 2000 S / m, the ratio of the thermal expansion coefficient of the filler to the polymer is less than or equal to 0.5, and the concentration of the filler phase in the composite material is greater than or equal to the filler concentration corresponding to the conductivity transition point of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to electro-optical displays and materials, particularly composite materials, used therein. The present invention relates in part to composite materials contained in adhesive or binder compositions having electrical and other properties that make them particularly suitable for use in electro-optical displays. Background Art

[0002] An electro-optical display comprises a layer of electro-optical material. The term "electro-optical" as applied to a material or display is used herein in its conventional sense in the field of imaging to refer to a material having a first display state and a second display state, the first display state and the second display state differing in at least one optical property, the material being caused to change from its first display state to the second display state by applying an electric field to the material. While the optical property is typically a color perceptible to the human eye, it may be another optical property such as light transmission, reflection, luminescence, or, in the case of a display for machine reading, a false color in the sense of a change in reflectivity of electromagnetic wavelengths outside the visible range.

[0003] Some electro-optic materials are solid in the sense that the material has a solid outer surface, but these materials may and often do have internal liquid or gas filled spaces. Such displays using solid electro-optic materials may be referred to hereinafter for convenience as "solid electro-optic displays". Thus, the term "solid electro-optic display" includes rotating two-color member displays, encapsulated electrophoretic displays, microcell electrophoretic displays, and encapsulated liquid crystal displays.

[0004] The terms "bistable" and "bistable" are used herein in their conventional sense in the art to refer to a display including a display element having a first display state and a second display state, the first display state and the second display state differing in at least one optical property such that after any given element is driven to assume its first or second display state with an addressing pulse of finite duration, that state will persist after termination of the addressing pulse for a time at least several times (e.g., at least 4 times) the minimum duration of the addressing pulse required to change the state of the display element. It is shown in U.S. Pat. No. 7,170,670 that some particle-based electrophoretic displays supporting grayscale can be stable not only in their extreme black and white states, but also in intermediate gray states, as well as some other types of electro-optical displays. This type of display is properly referred to as "multistable" rather than bistable, but for convenience, the term "bistable" may be used herein to cover both bistable and multistable displays.

[0005] Several types of electro-optical displays are known. One type of electro-optical display is a rotating two-color component type, such as described in, for example, U.S. Patent Nos. 5,808,783, 5,777,782, 5,760,761, 6,054,071, 6,055,091, 6,097,531, 6,128,124, 6,137,467, and 6,147,791 (although this type of display is generally referred to as a "rotating two-color ball" display, the term "rotating two-color component" is preferably more accurate because in some of the above-mentioned patents, the rotating component is not spherical). This display uses many small bodies (usually spherical or cylindrical) and internal dipoles, and the body includes two or more parts with different optical properties. These bodies are suspended in a liquid-filled vacuole in a matrix, and the vacuole is filled with liquid so that the body can rotate freely. The appearance of the display is changed by applying an electric field to the display, thereby rotating the body to various positions and changing the portion of the body that is seen through the viewing surface. This type of electro-optic medium is usually bistable.

[0006] Another type of electro-optical display uses an electrochromic medium, for example in the form of a nanochromic film, which includes an electrode formed at least in part from a semiconducting metal oxide and a plurality of dye molecules attached to the electrode that are capable of reversible color change; see, for example, O'Regan, B. et al., Nature 1991, 353, 737; and Wood, D., Information Display, 18(3), 24 (March 2002). See also Bach, U. et al., Adv. Mater., 2002, 14(11), 845. Nanochromic films of this type are also described, for example, in U.S. Patent Nos. 6,301,038, 6,870,657, and 6,950,220. This type of medium is also typically bistable.

[0007] Another type of electro-optical display is the electrowetting display developed by Philips and described in Hayes, RA et al., "Video-Speed ​​Electronic Paper Based on Electrowetting", Nature, 425, 383-385 (2003). It is shown in US Pat. No. 7,420,549 that such an electrowetting display can be made bistable.

[0008] One type of electro-optical display that has been the subject of intensive research and development for many years is a particle-based electrophoretic display, in which a plurality of charged particles move through a fluid under the influence of an electric field. Compared to liquid crystal displays, electrophoretic displays can have the properties of good brightness and contrast, wide viewing angles, state bistability, and low power consumption. However, problems with the long-term image quality of these displays have hindered their widespread use. For example, the particles that make up electrophoretic displays tend to settle, resulting in insufficient useful life for these displays.

[0009] As mentioned above, the electrophoretic medium requires the presence of a fluid. In most prior art electrophoretic media, the fluid is a liquid, but the electrophoretic medium can be produced using a gaseous fluid; see, for example, Kitamura, T. et al., "Electronic toner movement for electronic paper-like display", IDW Japan, 2001, Paper HCS 1-1, and Yamaguchi, Y. et al., "Toner display using insulative particles charged triboelectrically", IDW Japan, 2001, Paper AMD4-4). See also U.S. Patent Nos. 7,321,459 and 7,236,291. When such a gas-based electrophoretic medium is used in a direction that allows particle sedimentation, such as when used in a signboard where the medium is arranged in a vertical plane, such a gas-based electrophoretic medium is susceptible to the same type of problems due to the same particle sedimentation as a liquid-based electrophoretic medium. In fact, the particle sedimentation problem is more severe in gas-based electrophoretic media than in liquid-based electrophoretic media because the lower viscosity of the gaseous suspending fluid compared to liquids allows for faster sedimentation of the electrophoretic particles.

[0010] Numerous patents and applications assigned to or in the name of the Massachusetts Institute of Technology (MIT), Iink Corporation, Iink California LLC, and related companies describe various techniques for encapsulating and microcell electrophoretic and other electro-optical media. Encapsulated electrophoretic media include a number of small capsules, each of which itself includes an internal phase and a capsule wall surrounding the internal phase, wherein the internal phase contains electrophoretically movable particles in a fluid medium. Typically, the capsules themselves are held in a polymer binder to form a coherent layer located between two electrodes. In microcell electrophoretic displays, the charged particles and fluid are not encapsulated in microcapsules, but are retained in a plurality of cavities formed in a carrier medium (usually a polymer film). The techniques described in these patents and applications include:

[0011] (a) electrophoretic particles, fluids, and fluid additives; see, e.g., U.S. Pat. Nos. 7,002,728 and 7,679,814;

[0012] (b) capsules, binders and encapsulation processes; see, e.g., U.S. Pat. Nos. 6,922,276 and 7,411,719;

[0013] (c) microcell structures, wall materials, and methods of forming microcells; see, e.g., U.S. Pat. Nos. 7,072,095 and 9,279,906;

[0014] (d) Methods for filling and sealing microlocations; see, e.g., U.S. Pat. Nos. 7,144,942 and 7,715,088;

[0015] (e) Films and subassemblies containing electro-optical materials; see, e.g., U.S. Patent Nos. 6,982,178 and 7,839,564;

[0016] (f) Backplanes, adhesive layers and other auxiliary layers and methods for use in displays; see, e.g., U.S. Patent Nos. D485,294; 6,124,851; 6,130,773; 6,177,921; 6,232,950; 6,252,564; 6,312,304; 6,312,971; 6,376,828; 6,392,786; 6,413,790; 6,422,687; 6,445,374; 6,480,182; 6,498,114; 6,506,438; 6,518,949; 6,521,489; 6,535,197; 6,545,291; 6,639,578; 6 ,657,772;6,664,944;6,680,725;6,683,333;6,724,519;6,750,473;6,816,147;6,819,471;6,825,068;6,831,769;6,842,167;6,842,279;6,842, 657; 6,865,010; 6,873,452; 6,909,532; 6,967,640; 6,980,196; 7,012,735; 7,030,412; 7,075,703; 7,106,296; 7,110,163; 7,116,318; 7,148,128; 7 ,167,155;7,173,752;7,176,880;7,190,008;7,206,119;7,223,672;7,230,751;7,256,766;7,259,744;7,280,094;7,301,693;7,304,780;7,327 ,511;7,347,957;7,349,148;7,352,353;7,365,394;7,365,733;7,382,363;7,388,572;7,401,758;7,442,587;7,492,497;7,535,624;7,551,346; 7,554,712; 7,583,427; 7,598,173; 7,605,799; 7,636,191; 7,649,674; 7,667,886; 7,672,040; 7,688,497; 7,733,335; 7,785,988; 7,830,592; 7,843 ,626; 7,859,637; 7,880,958; 7,893,435; 7,898,717; 7,905,977; 7,957,053; 7,986,450; 8,009,344; 8,027,081; 8,049,947; 8,072,675; 8,077,141;8,089,453; 8,120,836; 8,159,636; 8,208,193; 8,237,892; 8,238,021; 8,362,488; 8,373,211; 8,389,381; 8,395,836; 8,437,069; 8,441,414; 8,456,589; 8,498,042; 8,514,168; 8,547,628; 8,576,162; 8,610,988; 8,714,780; 8,728,266; 8,743,077; 8,754,859; 8,797,258; 8,797,6 33; 8,797,636; 8,830,560; 8,891,155; 8,969,886; 9,147,364; 9,025,234; 9,025,238; 9,030,374; 9,140,952; 9,152,003; 9,152,004; 9,201,279; 9,223,164; 9,285,648; and 9,310,661; and U.S. Patent Application Publication Nos. 2002 / 0060321; 2004 / 0008179; 2004 / 0085619; 2004 / 0105036; 2004 / 0112525; 2005 / 0122306; 2005 / 0122563; 2006 / 0215106; 2006 / 0255322; 2007 / 0052757; 2007 / 0097489; 2007 / 0109219; 2008 / 0061300; 2008 / 0149271; 2009 / 0122389; 2009 / 0315044; 2010 / 0177396; 2011 / 0140744; 2011 / 0187683; 2011 / 0187689; 2011 / 0292319; 2013 / 0250397; 2013 / 0278900; 2014 / 007 8024; 2014 / 0139501; 2014 / 0192000; 2014 / 0210701; 2014 / 0300837; 2014 / 0368753; 2014 / 0376164; 2015 / 0171112; 2015 / 0205178; 2015 / 0226986; 2015 / 0227018; 2015 / 0228666; 2015 / 0261057; 2015 / 0356927; 2015 / 0378235; 2016 / 077375; 2016 / 0103380 and 2016 / 0187759; and International Application Publication No. WO 00 / 38000; European Patent No. 1,099,207B1 and 1,145,072B1;

[0017] (g) color formation and color adjustment; see, e.g., U.S. Pat. Nos. 7,075,502 and 7,839,564;

[0018] (h) Methods for driving displays; see, e.g., U.S. Patent Nos. 7,012,600 and 7,453,445;

[0019] (i) Display applications; see, e.g., U.S. Patent Nos. 7,312,784 and 8,009,348; and

[0020] (j) Non-electrophoretic displays, such as described in U.S. Patent No. 6,241,921 and U.S. Patent Application Publication No. 2015 / 0277160; and applications of packaging and microcell technology other than displays; see, for example, U.S. Patent Application Publication Nos. 2015 / 0005720 and 2016 / 0012710.

[0021] Many of the aforementioned patents and applications recognize that the walls surrounding discrete microcapsules in an encapsulated electrophoretic medium can be replaced by a continuous phase, thereby producing a so-called polymer-dispersed electrophoretic display, wherein the electrophoretic medium includes a plurality of discrete droplets of electrophoretic fluid and a continuous phase of polymer material, and the discrete droplets of electrophoretic fluid within such a polymer-dispersed electrophoretic display can be considered to be capsules or microcapsules, even though there is no discrete capsule membrane associated with each individual droplet; see, e.g., aforementioned U.S. Patent No. 6,866,760. Therefore, for the purposes of this application, such polymer-dispersed electrophoretic media are considered to be a subclass of encapsulated electrophoretic media.

[0022] Although electrophoretic media are typically opaque (because, for example, in many electrophoretic media, the particles substantially block visible light from being transmitted through the display) and are operated in a reflective mode, some electrophoretic displays can be made to operate in a so-called "shutter mode," in which one display state is substantially opaque and one display state is light transmissive. See, for example, U.S. Patents Nos. 5,872,552; 6,130,774; 6,144,361; 6,172,798; 6,271,823; 6,225,971; and 6,184,856. Dielectrophoretic displays, which are similar to electrophoretic displays but rely on changes in electric field strength, can operate in a similar mode; see U.S. Patent No. 4,418,346. Other types of electro-optical displays can also operate in a shutter mode. Electro-optical media operating in a shutter mode may be useful in multilayer structures for full color displays; in such structures, at least one layer adjacent to a viewing surface of the display is operated in a shutter mode to expose or hide a second layer further from the viewing surface.

[0023] Packaged electrophoretic displays are generally not plagued by the clustering and sedimentation failure modes of conventional electrophoretic devices and offer additional benefits, such as the ability to print or coat the display on a variety of flexible and rigid substrates. (The use of the word "printing" is intended to include all forms of printing and coating, including but not limited to: pre-metered coating such as patch die coating, slot or extrusion coating, slide or laminate coating, curtain coating; roll coating such as roller blade coating, forward and reverse roll coating; gravure coating; dip coating; spray coating; meniscus coating; spin coating; brush coating; air knife coating; screen printing process; electrostatic printing process; thermal printing process; inkjet printing process; electrophoretic deposition (see U.S. Patent No. 7,339,715); and other similar technologies.) Therefore, the resulting display can be flexible. In addition, because the display medium can be printed (using a variety of methods), the display itself can be inexpensively manufactured.

[0024] Electrophoretic displays typically include a layer of electrophoretic material and at least two other layers disposed on opposite sides of the electrophoretic material, one of the two layers being an electrode layer. In most such displays, both layers are electrode layers, and one or both electrode layers are patterned to define pixels of the display. For example, one electrode layer may be patterned as an elongated row electrode, while the other electrode layer may be patterned as an elongated column electrode extending at right angles to the row electrode, with the pixel being defined by the intersection of the row electrode and the column electrode. Alternatively, and more typically, one electrode layer has the form of a single continuous electrode, while the other electrode layer is patterned as a matrix of pixel electrodes, each pixel electrode defining a pixel of the display. In another type of electrophoretic display for use with a stylus, a print head, or a similar movable electrode separated from the display, only one of the layers adjacent to the electrophoretic layer includes an electrode, and the layer on the opposite side of the electrophoretic layer is typically a protective layer intended to prevent the movable electrode from damaging the electrophoretic layer.

[0025] The manufacture of a three-layer electrophoretic display typically involves at least one lamination operation. For example, in several patents and applications of MIT and Iink mentioned above, a process for manufacturing an encapsulated electrophoretic display is described, in which an encapsulated electrophoretic medium including capsules in a binder is applied to a flexible substrate containing indium tin oxide (ITO) or a similar conductive coating (as one electrode of the final display) on a plastic film, and the capsule / binder coating is dried to form a coherent layer of the electrophoretic medium firmly adhered to the substrate. Separately, a backplane containing an array of pixel electrodes and an appropriately arranged conductor for connecting the pixel electrodes to a drive circuit is prepared. To form the final display, the substrate with the capsule / binder layer is laminated to the backplane using a laminating adhesive. (A very similar process can be used to prepare an electrophoretic display that can be used with a stylus or similar movable electrode by replacing the backplane with a simple protective layer such as a plastic film on which a stylus or other movable electrode can slide). In a preferred form of this process, the backplane itself is flexible and is prepared by printing pixel electrodes and conductors on a plastic film or other flexible substrate. The obvious lamination technique for mass producing displays by this process is roll lamination using a laminating adhesive.

[0026] Electro-optical displays made using the above-mentioned front plane laminate or double release film usually have a laminating adhesive layer between the electro-optical layer itself and the backplane, and the presence of the laminating adhesive layer affects the electro-optical properties of the display. In particular, the conductivity of the laminating adhesive layer affects both the low temperature performance and the resolution of the display. The low temperature performance of the display (which has been found empirically) can be improved by increasing the conductivity of the laminating adhesive layer, for example by doping the layer with tetrabutylammonium hexafluorophosphate or other materials, as described in the above-mentioned U.S. Patent Nos. 7,012,735 and 7,173,752. However, increasing the conductivity of the laminating adhesive layer in this way tends to increase pixel flooding (the phenomenon that the area of ​​the electro-optical layer that changes the optical state in response to the voltage change at the pixel electrode is larger than the pixel electrode itself), which tends to reduce the resolution of the display. Therefore, this type of display obviously essentially requires a compromise between low temperature performance and display resolution, and in fact it is usually the low temperature performance that is sacrificed. In addition, since the conductivity of the laminating adhesive depends on the temperature, the temperature range in which the display can acceptably operate may be limited to a narrow temperature range. This limits the potential applications of the display to environments where temperature fluctuations are not significant.

[0027]

[0006] Therefore, there is a need for improved laminating adhesive compositions and other composite materials to provide electrophoretic displays having improved performance over a wider range of ambient temperatures. Summary of the invention

[0028] According to a first embodiment of the present invention, an electro-optic display is provided, which includes an electro-optic material layer, at least one conductor, and an adhesive material between the electro-optic material layer and the at least one conductor. At least one of the electro-optic material and the adhesive material includes a composite material, the composite material including a polymer phase and a filler phase, such that the volume fraction of the filler phase is about the percolation threshold. In addition, the filler phase may have a volume fraction greater than or equal to 0.5×10 3 The conductivity of the composite material may be 200 Å / s / m, the ratio of the thermal expansion coefficient of the filler to the polymer may be less than or equal to 0.5, and the concentration of the filler phase in the composite material may be greater than or equal to the filler concentration corresponding to the conductivity transition point of the composite material.

[0029] The composite materials according to various embodiments of the present invention are well suited for use in particle-based electrophoretic displays. However, these composite materials may also be used in other types of electro-optical displays, such as displays utilizing polymer dispersed liquid crystals.

[0030] These and other aspects of the invention will be apparent from the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings illustrate one or more embodiments according to the present concept by way of example only and not limitation.In the accompanying drawings, like reference numerals represent the same or similar elements.

[0032] Figure 1 is a schematic cross-sectional view of a front plane laminate of the present invention;

[0033] Figure 2 is a schematic cross-sectional view of a dual release film of the present invention;

[0034] Figure 3A and 3B is a schematic cross-section through an adhesive layer at two successive stages of the process of the present invention;

[0035] Figure 4 is a schematic side view of an apparatus that may be used to practice the process of the present invention; and

[0036] Figure 5 is a graph showing the relationship between the volume fraction of the polymer composite and the electrical conductivity.

[0037] Figure 6 is a line with lines y1 and y2 Figure 5 relationship diagram. DETAILED DESCRIPTION

[0038] In the following detailed description, many specific details are set forth by way of example in order to provide a thorough understanding of the relevant teachings. However, it should be apparent to those skilled in the art that the present teachings can be practiced without these details.

[0039] In a typical process for making an electro-optical display, two subassemblies are first made, one subassembly including the electro-optical layer and a first substrate, and a second subassembly including the second substrate; at least one subassembly (usually both) including an electrode. Furthermore, in one common form of this process for making an active matrix display, one subassembly includes the substrate, a single continuous ("common") electrode extending across a plurality of pixels (usually the entire display), and the electro-optical layer, while the second assembly (usually referred to as the "backplane") includes the substrate carrying a matrix of pixel electrodes defining the individual pixels of the display, as well as non-linear devices (usually thin-film transistors) and other circuitry for generating the electrical potentials on the pixel electrodes required to drive the display (i.e., switch the individual pixels to the optical state required to provide the desired image on the display). A laminating adhesive is disposed between the first and second subassemblies and adheres them together to form the final display.

[0040] Now refer to the accompanying drawings Figure 1 To describe the preferred lamination process of the present invention (but only as an example), Figure 1 is a schematic cross-sectional view through a subassembly (front plane laminate or FPL) used in the process of the present invention, the subassembly including a substrate, a conductive layer, an electro-optical layer, and an adhesive layer, the subassembly being shown at an intermediate stage in the process before the subassembly is laminated to a second subassembly.

[0041] Figure 1 The front plane laminate shown (generally designated 100) includes a light-transmitting substrate 110, a light-transmitting electrode layer 120 (note that this is not the electrode located on the side of the laminating adhesive opposite the electro-optic layer in the final electro-optic display), an electro-optic layer 130, a laminating adhesive layer 180 and a release sheet 190; the release sheet is shown as being in the process of being removed from the laminating adhesive layer 180 prior to laminating the FPL 100 to the backplane.

[0042] Substrate 110 is typically a transparent plastic film, such as a 7 mil (177 μm) polyethylene terephthalate (PET) sheet. The lower surface ( Figure 1 The substrate 110 may have one or more additional layers (not shown), such as a protective layer for absorbing ultraviolet radiation, a barrier layer for preventing oxygen or moisture from entering the final display, and an anti-reflective coating for improving the optical performance of the display. A thin light-transmitting conductive layer 120 (preferably made of ITO) is coated on the upper surface of the substrate 110 and serves as a common front electrode in the final display. PET films coated with ITO are commercially available.

[0043] The electro-optic layer 130 may be deposited on the conductive layer 120 (typically by slot coating), with the two layers being in electrical contact. Figure 1 The electro-optic layer 130 shown in is an encapsulated electrophoretic medium and includes microcapsules 140, each of which includes negatively charged white particles 150 and positively charged black particles 160 in a hydrocarbon-based fluid 165. The microcapsules 140 are held in a polymer binder 170. When an electric field is applied to the electro-optic layer 130, the white particles 150 move to the positive electrode and the black particles 160 move to the negative electrode, so that the electro-optic layer 130 appears white or black to an observer viewing the display through the substrate 110, depending on whether the conductive layer 120 is positive or negative relative to the adjacent pixel electrode in the backplane. As will be appreciated by those skilled in the art, the charged particles (150, 160) are not limited to black and white and can be any color.

[0044] FPL 100 is ideally prepared by applying laminating adhesive 180 in liquid form, conveniently by slot coating, onto release sheet 190, drying (or otherwise curing) the adhesive to form a solid layer, and then laminating the adhesive and release sheet to electro-optic layer 130, which has been previously applied to substrate 110 bearing conductive layer 120; such lamination may conveniently be accomplished using hot roll lamination. (Alternatively, but less ideally, the laminating adhesive may be applied to electro-optic layer 130 and dried or otherwise cured there before covering with release sheet 190.) Release sheet 190 is conveniently a 7 mil (177 μm) film; depending on the nature of the electro-optic medium used, it may be desirable to coat the film with a release agent such as silicone. Figure 1 As shown, release sheet 190 is peeled or otherwise removed from laminating adhesive 180 before FPL 100 is laminated to a backplane (not shown) to form a final display.

[0045] Front plane laminate 100 in Figure 1 1 and 2, which are shown in general form, which may be used throughout the scope of the present invention. The adhesive layer 180 incorporated into the FPL 100 may include a composite material having low thermal sensitivity, as will be described in more detail below.

[0046] Further details regarding the front plane laminate and processes for making and using the same are described in the aforementioned U.S. Patent No. 6,982,178 and U.S. Patent Application Publication No. 2009 / 0225397, the contents of which are incorporated herein by reference in their entirety.

[0047] Figure Figure 2 FIG. 2 shows a double release sheet (generally designated 300) according to another embodiment of the present invention. The double release sheet 300 includes a central layer 302 of electro-optical material, specifically Figure 23 is a layer including a capsule 304 in a polymer binder 306. The capsule 304 may be similar to the above reference Figure 1 Sheet 300 also includes a first adhesive layer 308, a first release sheet 310 covering first adhesive layer 308, a second adhesive layer 312 disposed on a side of layer 302 opposite first adhesive layer 308, and a second release sheet 314 covering second adhesive layer 312.

[0048] Sheet 300 may be formed by first coating a release sheet 310 with an adhesive layer, which is then dried or cured to form a first adhesive layer 308. Next, a mixture of capsules 304 and binder 306 is printed or otherwise deposited on first adhesive layer 308, which is then dried or cured to form a coherent layer 302. Finally, an adhesive layer is deposited on layer 302, dried or cured to form a second adhesive layer 312, and covered by a second release sheet 314.

[0049] It will be apparent to those skilled in the art of coating technology that this sequence of operations for forming sheet 300 is well suited for continuous production and that, with careful selection of materials and process conditions, the entire sequence of operations can be performed at one time by conventional roll-to-roll coating equipment.

[0050] In order to assemble a display using a double release film such as film 300, one release sheet (usually coated with an electro-optical material) is peeled off, and the remaining layer of the double release film is attached to the front substrate using, for example, a lamination process based on heat, radiation or chemistry. Typically, the front substrate will include a conductive layer that will form the front electrode of the final display. The front substrate may include additional layers, such as an ultraviolet filter or a protective layer intended to protect the conductive layer from mechanical damage. Afterwards, the other release sheet is peeled off, thereby exposing a second adhesive layer for attaching the electro-optical material coated assembly to the backplane. Similarly, a lamination process based on heat, radiation or chemistry can be used. It should be understood that the order of the two laminations described is essentially arbitrary and can be reversed, but in practice it is almost always more convenient to laminate the double release film to the front substrate first and then laminate the resulting front subassembly to the backplane.

[0051] Further details regarding dual release films and processes for making and using them are disclosed in US Patent Application Publication No. 2004 / 0155857, the contents of which are incorporated herein by reference in their entirety.

[0052] Either or both of adhesive layers 308 and 312 may include a composite material including a polymer phase and a filler phase. The concentration of the filler phase is selected so that the composite system exhibits a low temperature dependence of its conductivity over a temperature range relevant to display operation.

[0053] The filler phase added to the polymer phase of the composite system preferably has a greater conductivity than the polymer phase, so that adding more filler to the polymer phase increases the conductivity of the composite. In addition, preferably, the coefficient of thermal expansion (CTE) of the filler is significantly less than the coefficient of thermal expansion of the polymer composite. For example, a composite material comprising a polyurethane for the polymer phase and a metal needle or flake (e.g., aluminum or nickel) can be provided. The CTE of the polyurethane can be in the range of 60 to 200 ppm / K. The CTE of aluminum is about 22 ppm / K. The CTE of nickel is about 13 ppm / K. The ratio of the CTE of the filler phase to the CTE of the polymer phase is preferably 0.5 or less, more preferably 0.3 or less, and most preferably 0.1 or less.

[0054] In order to suppress the effect of temperature on the conductivity of the composite, the filler is added to the composite in an amount of about the percolation threshold. As used in this specification and claims, "percolation threshold" refers to the filler volume fraction in a composite material comprising a polymer phase and a filler phase, below which the composite exhibits a conductivity whose logarithm is closer to that of the polymer phase than to that of the filler phase, and above which the composite exhibits a conductivity whose logarithm is closer to that of the filler phase than to that of the polymer phase.

[0055] By ensuring that the volume fraction of the filler in the polymer matrix is ​​around the percolation threshold, the conductivity of the composite is limited even with large temperature fluctuations. Figure 5 , provides a representative plot of the electrical conductivity of a polymer composite (y-axis) versus the volume fraction of filler in the polymer composite (x-axis). Point 400 on the plot is the percolation threshold.

[0056] If the thermal expansion coefficient of the polymer phase in the composite is much greater than that of the filler, the volume fraction of the filler phase in the composite will decrease with increasing temperature. For example, if the initial volume fraction φ of the filler in the composite is about the percolation threshold (400), the conductivity of the composite will decrease significantly with increasing temperature because the filler concentration will decrease. This can counteract the natural tendency of the unfilled polymer matrix to increase in conductivity at high temperatures. As the temperature decreases, the polymer phase will shrink more than the filler, causing the volume fraction of the filler to increase. Therefore, if the initial volume fraction of the filler in the composite is about the percolation threshold (400), the conductivity of the composite will increase with decreasing temperature.

[0057] Thus, by incorporating fillers having a significantly smaller coefficient of thermal expansion than the polymer phase into the composite, and loading the composite with fillers about the percolation threshold, the fractional change in conductivity with temperature that would otherwise be exhibited by an unfilled polymer material can be reduced. In other words, the tendency for conductivity to increase with increasing temperature and for conductivity to decrease with decreasing temperature is reduced. Composite materials according to various embodiments of the present invention can provide materials having much less variation in fractional variation in conductivity over a temperature range of interest than would be found from using an unfilled polymer.

[0058] As used throughout the specification and claims, the phrase "about the percolation threshold" refers to a filler concentration (volume percent) at or above the conductivity transition point. The conductivity transition point can be calculated from the conductivity curve of the composite material, such as Figure 5 and Figure 6 Reference Figure 6 , a first line y1 is drawn through the points on the conductivity curve of the composite material at a filler concentration of zero, and the slope m1 of line y1 is equal to the slope of the conductivity curve at a filler concentration of zero. A second line y2 is drawn through the points on the conductivity curve corresponding to the percolation threshold, and the slope m2 of line y2 is equal to the slope of the conductivity curve at the percolation threshold. Figure 6 The intersection 402 of the two lines y1 and y2 provides the conductivity transition point. The filler concentration at the conductivity transition point can be calculated, for example, using the following equations (1) and (2) for y1 and y2:

[0059] y1=m1*(φ)+b1 Equation 1

[0060] y2=m2*(φ)+b2 Equation 2

[0061] At the conductivity transition point, y1 equals y2, so:

[0062] m1*(φ)+b1=m2*(φ)+b2

[0063] Solving for “φ” yields equation (3):

[0064] φ=(b2-b1) / (m1-m2) Equation 3

[0065] Therefore, the filler concentration at the conductivity transition point is equal to the ratio of the difference between the y-intercepts of y2 and y1 to the difference between the slopes of y1 and y2.

[0066] Preferably, the composite materials used in various embodiments of the present invention exhibit a variation in conductivity with temperature, i.e., (1 / s)*ds / dT, that is less than or equal to 60% of the variation in conductivity with temperature of the unfilled polymer, more preferably less than or equal to 30%, and most preferably less than or equal to 10%.

[0067] When the composite is incorporated into an adhesive layer of an electro-optical display, the polymer phase of the composite material according to various embodiments of the present invention is preferably an anisotropic laminating adhesive having a greater electrical conductivity in the direction from the electrode to the electro-optical material than in the plane of the layer. Such anisotropic adhesives produce only a small voltage drop between the electrode and the electro-optical material (thus allowing the electric field across the electro-optical material layer to be as large as possible), while having a high resistance to the flow of current between adjacent electrodes, thereby minimizing crosstalk between adjacent pixels of the display.

[0068] Laminating adhesive can be hot melt adhesive, but can also be thermosetting, radiation-cured or pressure-sensitive adhesive. Adhesive can be based on ethylene vinyl acetate, acrylic acid, polyolefin, polyamide, polyester, polyurethane, silicone, epoxy resin, polyvinyl butyrate, polystyrene-butadiene or vinyl monomer or oligomer. In order to provide necessary anisotropic conductivity, adhesive can load conductive particles, such as carbon particles, silver particles, plated polymer balls, plated glass balls, indium tin oxide particles or nano-phase indium tin oxide particles. Alternatively, conductive polymers can be used, such as polyacetylene, polyaniline, polypyrrole, poly-(3,4-ethylenedioxythiophene) (PEDOT) or polythiophene come doped polymers, and make it in z-axis direction (perpendicular to the thickness of adhesive layer) rather than in the plane of this layer good conduction. In order to make these films, the adhesive sheet can be cast, then stretched on one or two axes, to introduce necessary anisotropic conductivity. Various types of anisotropic adhesives are described in U.S. Pat. Nos. 6,365,949, 5,213,715, and 4,613,351, and are commercially available, for example, from Minnesota Mining and Manufacturing Company (“3M”); Henkel Loctite Corporation, 1001 Trout Brook Crossing, Rocky Hill CT 06067; Btech Corporation, 8395 Greenwood Drive, Longmont CO 80503; and Dana Enterprises International, 43006 Osgood Road, Fremont CA 94539.

[0069] It is generally preferred that the anisotropic adhesives used in various embodiments of the present invention have an in-plane conductivity of less than about 10 -10 S / cm, and the conductivity in the z-direction is greater than about 10 -9 S / cm.

[0070] A process for forming a composite material according to one embodiment of the present invention is also provided. The composite material can be provided in the form of an anisotropic adhesive layer having a conductivity perpendicular to the plane of the layer that is greater than the conductivity in a parallel direction. The process includes: dispersing a plurality of conductive filler particles in an adhesive matrix, the particles having a conductivity different from that of the matrix; applying an electric field or a magnetic field to the particle / matrix mixture to effectively cause the particles to form conductive chains extending substantially perpendicular to the plane of the layer; and increasing the viscosity of the matrix (usually by gelling or curing the matrix) to prevent the particles from moving out of the chains.

[0071] In the attached figure Figure 3A and Figure 3B The use of electrorheological and magnetorheological effects to produce anisotropic conductive films by the process of the present invention is shown in a highly schematic manner in FIG. The electrorheological (ER) effect is an effect by which an electric field is applied to a particulate dispersion (e.g., a dispersion contained between parallel plate electrodes) so that the particles constituting the dispersion form chains or needle-like agglomerates. Figure 3A As shown, the process begins by forming a layer of conductive particles 12 dispersed in a matrix (continuous phase) of a laminating adhesive 14. An electric or magnetic field is applied perpendicular to the plane of the layer, causing the particles 12 to form chains 16 extending through the thickness of the layer, such as Figure 3B Finally, the viscosity of the matrix 14 is greatly increased, typically by gelling or curing the matrix, to prevent further movement of the particles 12 through the matrix 14, thereby locking the chains 16 in place.

[0072] When the complex conductivity (k*) of the particles is significantly higher than that of the matrix, chains parallel to the electric field lines are formed. Figure 3A shown) is dispersed in a low conductivity matrix (k m <10 -11 S / cm) of relatively high conductivity particles (k p >10 -9 S / cm). By applying an electric field to the dispersion, the particles are aligned in the z-axis direction, and the resulting z-axis chains are locked in place by curing or gelling the matrix. Since the chains are spaced laterally and are therefore separated by the low conductivity matrix, the final adhesive film contains only conductive chains that span or percolate in the z-axis direction. Z-axis conduction will be controlled by the conductivity of the chains, and therefore by the particle conductivity, while lateral conductivity will be controlled by the conductivity of the continuous low conductivity matrix.

[0073] The method is particularly suitable for preparing continuous films of z-axis laminating adhesives. For example, a continuous film z-axis conductive adhesive can be prepared by feeding a uniform dispersion of conductive particles in a low conductivity adhesive matrix into a coating die and coating the dispersion into a thin film (typically 10-100 μm thick), followed by application of an electric field and curing or gelling.

[0074] The magnetorheological process used to produce z-axis conductive adhesives is similar to the electrorheological process; magnetic particles are dispersed in a nonmagnetic adhesive matrix, the particles are aligned into chains in the z-axis direction by applying a magnetic field, and the chains are locked by curing or gelling of the matrix. In this case, the particles need to be magnetically polarizable and have a conductivity in the above range, typically greater than 10 -9 The range of particles that meet these requirements for magnetorheological processes may be more limited than the range of particles suitable for electrorheological processes, but magnetorheological processes are preferred because application of the magnetic field to the layer does not require electrical contact with the surface of the layer, so a water-based adhesive matrix can be used, which is not generally the case for electrorheological processes.

[0075] In the electrorheological process for producing a composite material comprising the laminating adhesive composition as a polymer matrix, the conductive particles used as fillers may preferably have a carbon content of not less than 0.5×10 -9 S / cm, 0.5×10 -7 S / m, 0.5×10 -5 S / m, 0.5×10 -3 S / m, 0.5×10 -1 S / m, 5S / m, 0.5×10 3 S / m, 0.5×10 5 S / m, 0.5×10 6 S / m, 10×10 6 S / m and 20×10 6 S / m (in increasing preference in the order given), and a diameter no greater than about 1 / 10 of the final film thickness. (The term "diameter" as used herein includes what is commonly referred to as the "equivalent diameter" of non-spherical particles, i.e., the diameter of a spherical particle having the same volume as the non-spherical particle.) The particles can be formed from semiconducting polymers such as acid-doped polyaniline, polythiophene, and pyrolyzed polyacrylonitrile. Alternatively, the particles can be formed from low-k* materials that are "activated" (increased) to a higher k* (relative to the k* of the matrix) by adding trace amounts of polar materials (e.g., water or ethylene glycol) that are primarily adsorbed on the surface of the particles. Suitable low-k* materials include cellulosic materials and various aluminas, silicates, and zeolites. The matrix (continuous phase) should have a relatively low conductivity relative to the particles, preferably less than 10 -10S / cm. Many low conductivity, low viscosity oils such as hydrocarbons used as fluids in many encapsulated electrophoretic media may be suitable; however, the matrix must also act as an adhesive and can gel or solidify to lock into the z-axis chains formed in the process. For example, thermoreversible gelling materials such as Kraton (registered trademark) rubber (block copolymer) or polyurethane may be particularly advantageous as a continuous phase, alone or in combination with a diluent to reduce the viscosity for coating and particle arrangement. Typical non-aqueous pressure-sensitive adhesives such as polyacrylate solutions, or succinate-functionalized hydrocarbon polymers, such as ethylene propylene copolymers, or silicone rubber-type adhesives may also be used. For gelling-type matrices, coating and particle arrangement occur under conditions where the material is not gelled, and then after the chains are formed, the matrix gels, such as by reducing the temperature or by adding or removing chemical components or reactants or exposing to a UV light source to crosslink the matrix. For solvent-based non-aqueous adhesives, the chains can be locked in place by rapid evaporation of the solvent.

[0076] Since the magnetorheological process differs from the electrorheological process only in that the chains are formed by magnetic field alignment rather than electric field alignment, the magnetorheological process of the present invention can use any type of matrix discussed above. However, since the magnetorheological process can use aqueous matrices as well as non-aqueous matrices, polyurethane adhesives, gelatin or other aqueous continuous phases can also be used. Particles suitable for magnetorheological processes include iron and other magnetizable materials, such as nickel and carbonyl iron; these materials are typically provided in particle sizes greater than 1-10 μm, which may not be optimal for preparing adhesive films, but they can be ground to smaller sizes for use in this process. Iron oxides, such as the γ-Fe2O3 material used in the magnetic recording industry, are typically provided in smaller particle sizes (about 10-100 nm) and can therefore be used in the preparation of films.

[0077] The criteria for particles used in the magnetorheological process of the present invention are slightly different from most other applications of magnetorheological particles. The process does not require a strong saturation magnetization (a typical criterion for selecting particles for magnetorheological fluids), but in the process the particles should be conductive enough to meet the z-axis conductivity ranges mentioned above.

[0078] The laminating adhesive film comprising the composite material described above can then be laminated to an electro-optical material and ultimately to an active matrix backplane while maintaining the anisotropic conductivity of the adhesive since the film never experiences large scale flow (relative to chain length) during the lamination process.

[0079] Any anisotropic z-axis conductive adhesive based on conductive chains or similar conductive areas within an intrinsically non-conductive matrix should have sufficient chains or conductive areas per unit area for each pixel of electro-optical material (used with the adhesive to experience a substantially uniform or uniform electric field over its entire area), otherwise undesirable optical effects may occur. The chain density per unit area can be adjusted, for example, by varying the conductive particle size, the volume fraction of the conductive particles, and the intensity and duration of the alignment field, thereby allowing the fine structure of the anisotropic adhesive to be varied.

[0080] Several types of lamination processes can be used for the fabrication of electrophoretic devices, including batch unit operations. Figure 4 A preferred process of this type is shown in a highly schematic manner and in side view in FIG. As shown, the process forms a display by converging two webs 202 and 204. Web 202 includes a rear electrode assembly on a flexible substrate, but Figure 4 Similarly, web 204 includes a flexible substrate, a transparent electrode layer such as an ITO layer, and a dry film of capsules and adhesive, but similarly Figure 4 The individual components are not shown. Figure 4 As shown, web 202 is unwound from feed reel 206 and brought electrode side up under mold 208 to be coated with a thin layer of radiation-curable laminating adhesive 210. Adhesive 210 can be cured by visible light, ultraviolet light, or electron beam radiation, for example. Web 202 with adhesive 210 passes through radiation source 212, the intensity of which is adjusted according to the catalyst concentration (and therefore the curing speed) of adhesive 210 and the speed of web 202. (If an anisotropic adhesive is being used, an electric or magnetic head can be provided between mold 208 and radiation source 212 to form the desired conductive particle chains before the matrix is ​​cured or gelled by radiation source 212.)

[0081] The web 204 is unwound from the feed reel 214 and the dried capsule-containing layer is conveyed to a convergence point 216 where the webs 202 and 204 are brought together. At this convergence point 216, the radiation-curable resin 210 is still in liquid form and readily fills the voids on the surface of the capsule-containing layer. The combination of web speed, catalyst concentration, and radiation intensity is adjusted to provide a curing rate such that hardening occurs after the convergence point 216 while the two webs 202 and 204 are held together by rollers 218. Finally, the resulting laminated web 220 is wound on a take-up reel 222.

[0082] It can be seen that the above described process allows the lamination process to be operated in-line, thus being able to achieve higher production rates than the batch unit processes previously discussed.

[0083] In another embodiment of the present invention, the composite material can be incorporated into the electro-optical material layer of the display. Specifically, the composite material can be incorporated into the binder of the encapsulation medium or the polymer film used to form the microunit. When the temperature and humidity of the environment change in the range of 10-50°C and 10-90% relative humidity (RH), the volume resistivity of some adhesives or polymer film materials changes by more than two orders of magnitude. In order to obtain satisfactory performance, it has been found that the change in the volume resistivity of the adhesive / film material should not exceed about 10 times within the range of 10-90% RH and 10-50°C or within any wider range of RH and temperature in which the display is expected to operate. Ideally, the change in volume resistivity does not exceed about 3 times within the specified RH and temperature range, and preferably does not exceed about 2 times.

[0084] In order to limit the thermosensitivity of the binder / membrane material to temperature and RH, fillers can be combined in the binder / membrane material to provide a composite similar to the above-mentioned composite material. In a polymer matrix with a thermal expansion coefficient larger than that of the filler, a conductive filler about the percolation threshold will similarly limit the influence of temperature on the resistivity of the binder / membrane. For example, as the temperature increases, the polymer phase will expand at a rate faster than the filler phase. If the volume fraction of the filler phase is about the percolation threshold, the resistivity of the composite material will decrease with the increase of temperature. When the temperature decreases, the polymer phase will shrink at a higher rate, so that the volume fraction of the filler increases, thereby reducing the resistivity of the composite. Therefore, compared with the binder / membrane without any filler, the composite material according to various embodiments of the present invention can provide a binder / membrane with reduced thermosensitivity.

[0085] Examples of acceptable binder materials include, but are not limited to, aliphatic polyurethanes that do not contain aromatic materials, such as NeoResin R 9630, NeoResin R 9330, NeoResin R 9314, NeoResin R 9314, NeoResin 9621, and mixtures thereof. Preferably, the binder should have a volume resistivity measured at 10°C that does not change by more than about 3 times after being maintained at 25°C and 45% relative humidity for 1000 hours. The wording "maintained" is intentionally used to emphasize that when testing binders to determine whether they meet the requirements of this aspect of the invention, care should be taken to ensure that the binder material is equilibrated with the specified atmosphere within a reasonable time. If the binder material is tested in a thick layer, the binder material may not be able to equilibrate with the specified atmosphere for a considerable period of time, and misleading results may be obtained. Such misleading results can be avoided by successively testing thinner layers of the binder material and checking whether the results are consistent. For sufficiently thin layers, it is sufficient to simply store the binder material under specified conditions for a specified time.

[0086] When testing materials for volume resistivity variations with RH and temperature, the same precautions described above should be followed to ensure that the sample being tested is truly equilibrated with the atmosphere at the desired RH and temperature before measuring volume resistivity.

[0087] The polymer material that can be used to form the micro-unit includes thermoplastics, thermosetting plastics or their precursors. Examples of thermoplastic or thermosetting precursors may include, but are not limited to, multifunctional acrylates or methacrylates, multifunctional vinyl ethers, multifunctional epoxides and oligomers or polymers thereof. Crosslinkable oligomers that impart flexibility, such as urethane acrylates or polyester acrylates, may also be added to improve the flexural resistance of the embossed micro-units.

[0088] Another embossable composition for the micro-unit may include a polar oligomer or polymer material. Such a polar oligomer or polymer material may be selected from oligomers or polymers having at least one group, such as a nitro group (-NO2), a hydroxyl group (-OH), a carboxyl group (-COO), an alkoxy group (-OR, wherein R is an alkyl group), a halogen (such as fluorine, chlorine, bromine or iodine), a cyano group (-CN), a sulfonate (-SO3), etc. The glass transition temperature of the polar polymer material is preferably below about 100°C, and more preferably below about 60°C. Specific examples of suitable polar oligomeric or polymeric materials may include, but are not limited to, polyhydroxy-functional polyester acrylates (e.g., BDE 1025, Bomar Specialties Co, Winsted, CT) or alkoxylated acrylates, such as ethoxylated nonylphenol acrylate (e.g., SR504, Sartomer), ethoxylated trimethylolpropane triacrylate (e.g., SR9035, Sartomer), or ethoxylated pentaerythritol tetraacrylate (e.g., SR494 from Sartomer).

[0089] Another type of embossable composition for forming microcells includes (a) at least one bifunctional UV curable component, (b) at least one photoinitiator, and (c) at least one release agent. Suitable bifunctional components may have a molecular weight greater than about 200. Bifunctional acrylates are preferred, and bifunctional acrylates having a urethane or ethoxylated backbone are particularly preferred. More specifically, suitable bifunctional components may include, but are not limited to, diethylene glycol diacrylate (e.g., SR230 from Sartomer), triethylene glycol diacrylate (e.g., SR272 from Sartomer), tetraethylene glycol diacrylate (e.g., SR268 from Sartomer), polyethylene glycol diacrylate (e.g., SR295, SR344, or SR610 from Sartomer), polyethylene glycol dimethacrylate (e.g., SR603, SR644, SR252, or SR74 from Sartomer), and poly(ethylene glycol) dimethacrylate (e.g., SR604, SR605, SR606, SR607, SR608, SR609, SR610, SR611, SR613, SR614, SR615, SR616, SR617, SR618, SR619, SR620, SR621, SR623, SR624, SR630, SR631, SR632, SR633, SR634, SR635, SR636, SR637, SR638, SR639, SR640, SR641, SR642, SR643, SR644, SR645, SR646, SR647, SR648, SR649, SR650, SR651, SR65 0), ethoxylated bisphenol A diacrylate (e.g., CD9038, SR349, SR601 or SR602 from Sartomer), ethoxylated bisphenol dimethacrylate (e.g., CD540, CD542, SR101, SR150, SR348, SR480 or SR541 from Sartomer), and polyurethane diacrylate (e.g., CN959, CN961, CN964, CN965, CN980 or CN981 from Sartomer; Ebecryl 230, Ebecryl 270, Ebecryl 8402, Ebecryl 8804, Ebecryl 8807 or Ebecryl 8808 from Cytec). Suitable photoinitiators may include, but are not limited to, bisacylphosphine oxide, 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2-isopropyl-9H-thioxanthen-9-one, 4-benzoyl-4'-methyldiphenyl sulfide and 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2,2-dimethoxy-1,2-diphenylethane-1-one or 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropane-1-one.Suitable release agents may include, but are not limited to, organically modified silicone copolymers such as silicone acrylates (e.g., Ebercryl 1360 or Ebercyl 350 from Cytec), silicone polyethers (e.g., Silwet 7200, Silwet 7210, Silwet 7220, Silwet 7230, Silwet 7500, Silwet 7600, or Silwet 7607 from Momentive). The composition may also optionally include one or more of the following components: a co-initiator, a monofunctional UV curable component, a multifunctional UV curable component, or a stabilizer.

[0090] The materials used as the filler phase in the binder material may be the same as those previously listed for the composites incorporated in the above-described laminating adhesive compositions.

[0091] The electro-optic medium present in a display manufactured according to various embodiments of the present invention may be of any type previously discussed. Thus, the electro-optic medium within a binder may include, for example, dispersed droplets of colored charged particles optionally encapsulated in microcapsules or microcells, droplets containing rotating multi-color or bi-color particles encapsulated in a dispersion, or an electrochromic medium. However, it is generally preferred that the electro-optic medium is an electrophoretic medium comprising a plurality of capsules, each capsule comprising a capsule wall and an internal phase, the internal phase comprising charged particles in a fluid and capable of moving through the fluid when an electric field is applied to the electrophoretic medium, the electrophoretic medium further comprising a polymer binder within which the capsules are held.

[0092] In addition to including the composite materials of the present invention, the electrophoretic media and displays of the present invention may employ the same components and manufacturing techniques as those of the aforementioned Iink and MIT patents and applications. The reader is referred to these patents and applications, particularly the aforementioned U.S. Patent No. 6,831,769, for details of preferred materials and processes for producing encapsulated electrophoretic displays.

[0093] Although preferred embodiments of the present invention have been shown and described herein, it should be understood that such embodiments are provided by way of example only. Without departing from the spirit of the present invention, those skilled in the art will appreciate many variations, changes and substitutions. Therefore, the appended claims are intended to encompass all these variations that fall within the spirit and scope of the present invention.

Claims

1. An electro-optical display comprising: electro-optical material layer, at least one conductor, and an adhesive material between the layer of electro-optical material and the at least one conductor, Wherein, at least one of the electro-optical material and the adhesive material comprises a composite material, wherein the composite material comprises a polymer phase and a filler phase, wherein the filler phase has a molecular weight greater than or equal to 0.5×10 3 S / m, the ratio of the thermal expansion coefficient of the filler to that of the polymer is less than or equal to 0.5, and The concentration of the filler phase in the composite material is greater than or equal to a filler concentration corresponding to a conductivity transition point of the composite material.

2. The electro-optical display according to claim 1, wherein: The composite material exhibits a rate of change in electrical conductivity with temperature that is less than or equal to 60% of the rate of change in electrical conductivity with temperature of the polymer phase alone.

3. The electro-optical display according to claim 1, wherein: The filler phase has a value greater than or equal to 10×10 6 Conductivity in S / m.

4. The electro-optical display according to claim 1, wherein: The filler phase has a value greater than or equal to 20×10 6 Conductivity in S / m.

5. The electro-optical display according to claim 1, wherein: The ratio of the thermal expansion coefficients of the filler and the polymer is less than or equal to 0.

3.

6. The electro-optical display according to claim 1, wherein: The ratio of the thermal expansion coefficients of the filler to the polymer is less than or equal to 0.

1.

7. The electro-optical display according to claim 1, wherein: The electro-optical material includes a binder comprising droplets of a dispersion.

8. The electro-optical display according to claim 7, wherein: The droplets are encapsulated within microcapsules.

9. The electro-optical display according to claim 7, wherein: The binder includes the polymer phase and the filler phase.

10. The electro-optical display according to claim 7, wherein: The dispersion includes charged particles dispersed in a solvent.

11. The electro-optical display according to claim 10, wherein: The charged particles include a plurality of colored particles.

12. The electro-optical display of claim 1, wherein: The electro-optic material includes a binder containing a plurality of multi-color particles encapsulated in a dispersion.

13. An electro-optical display according to claim 12, wherein: The binder includes the polymer phase and the filler phase.

14. The electro-optical display of claim 12, wherein: The multicolor particles are bicolor.

15. The electro-optical display of claim 1, wherein: The electro-optical material includes a polymer film having a plurality of micro-units.

16. An electro-optical display according to claim 15, wherein The polymer film includes the polymer phase and the filler phase.

17. The electro-optical display of claim 15, wherein: The microlocations comprise a dispersion of charged particles dispersed in a solvent.

18. An electro-optical display according to claim 17, wherein: The charged particles include a plurality of colored particles.

Citation Information

Patent Citations

  • Electronic display

    EP1099207B1

  • Method of addressing microencapsulated display media

    EP1145072B1

  • Minimally- patterned, thin-film semiconductor devices for display applications

    US20020060321A1

  • Electrode and connecting designs for roll-to-roll format flexible display manufacturing

    US20040008179A1

  • Novel Methods and compositions for improved electrophoretic display performance

    US20040085619A1